RAHASIA DAGANG SEBAGAI SALAH SATU PERLINDUNGAN HAK KEKAYAAN INTELEKTUAL DARI HASIL PENELITIAN HIBAH SEKOLAH VOKASI IPB TAHUN 2020: Trade Secrets as The Intellectual Property Rights Protections of The College of Vocational Studies IPB University’s Grant Research in 2020 - Faranita Ratih Listiasari (IPB University, 2021)
ABSTRACTThe Research results as the result of thoughts from researchers or lecturers need to be protected from harmful fraudulent actions. Protection of the research results also provides motivation for researchers or lecturers to continue working. One form of protection provided is the protection of Intellectual Property Rights (IPR). Various forms of IPR can be utilized as long as it meets the criteria of the IPR field. The purpose of this study was to determine the form of protection of trade secrets for the Research Results. In addition, to find out the efforts that need to be made to fulfill trade secret requirements. This research is normative legal research with a qualitative approach. The Research results of The College of Vocational Studies IPB University’s lecturer who research grants in 2020 that can be given protection as trade secrets. The Research results can be protected as trade secrets if they meet the criteria that the research results are confidential information in the field of technology and/or business, have economic value and are kept confidential by researchers or lecturers. To maintain the confidentiality of the research results, efforts were made such as providing a password, writing the word